METAPHOR IN THE POETRY “I AM A COLD HEART HUMAN” BY GALIH PANDHU (ON TELEGRAM) - fahdilla dilla; Anggie Nadia Harahap; Emeliya Sukma Dara Damanik; M. Farhan Husaini Siregar; Noni Sulistia (EJI (English Journal of Indragiri) : Studies in Education, Literature, and Linguistics, 2022)
This study aims to analyze the metaphors contained in the poem entitled "I am a Cold-heart Human" by Galih Pandhu. The use of the word metaphor is not only found in songs, movie, short stories, and also in everyday life, but metaphors are also found in poetry, therefore researchers are interested in the metaphors contained in poetry. This study uses a qualitative method, data collection is collected then the researcher investigates the metaphor contained in the poem entitled "I am a Cold-heart Human" by Galih Pandhu, then the data taken and collected is analyzed using the theories contained in the metaphor so that it can support the research. Metaphor is a comparative language style that has 4 types, namely Anthropomorphic Metaphors, Animal Metaphors, Concrete to Abstract Metaphors, and Synthetic Metaphors.